A study of internet addiction and its association with personality traits, depression and anxiety symptoms among young adults in Klang Valley, Malaysia - Wah, Lee Chung (2016)
Background: The internet is now playing an important role in the developed as well as the developing countries in terms of information access, networking, communication and the way interaction is being carried out. It no doubt has become an invaluable tool of the era. However, it has also been found to have negative impacts upon the psychological health of its users when the way it is used has become pathological. It has also been found that certain personality traits are associated to the addiction of the internet. Objectives: This study aimed to determine the prevalence of internet addiction, and its association with anxiety, depression and personality traits based on the alternative five model among the young adult allied health students who are being posted in Hospital Tengku Ampuan Rahimah, Klang. Method: A cross sectional study which uses convenience sampling method in recruiting the 267 samples of young adults allied health students attached to the hospital during the period of November 2015 to January 2016. A questionnaire in related to demographic details and internet use habits were distributed along with the validated Malay version of Internet Addiction Test, the validated Malay version of Hospital Anxiety and Depression Scale and the validated Malay version of Zuckerman-Kuhlman Personality Questionnaire-40-Cross Culture Scale. Data analysis were done using the Statistical Package for Social Sciences (SPSS) version 22 by using Pearson Chi Square test and Multiple Logistic Regression analysis to investigate for the association of anxiety, depression and personality traits with internet addiction, and sociodemographic factor and internet use habits as possible confounding factors. Results: There were 267 adult samples of age 18 to 24 years old and 30.7% are moderately addicted to the internet and 1.1% of are severely addicted. Pearson Chi-square test have shown no significant association between internet addiction and anxiety (df) 0.822 (1), p=0.365, whereas internet addiction is significantly associated to depression (df) 13.352 (1), p<0.001. Multiple logistic regression analysis showed that Impulsivity-Sensation Seeking trait (p-value=0.021), Neuroticism-Anxiety trait (p-value<0.001), and the online activity of e-mailing (p-value=0.034) to be associated to internet addiction. Conclusion: The results suggest that depression and the personality trait of Impulsivity-Sensation Seeking and Neuroticism-Anxiety is significantly associated with internet addiction. Depressed patients and patients who exhibit such personality traits need to be also considered for the possibility of internet addiction.